Conical intersection dynamics in a rhodopsin analog: 9-cis isorhodopsin - Polli, D; Brida, D; Manzoni, C; Spillane, K; Garavelli, M; Kukura, P; Mathies, R; Cerullo, G (2011)
Using broadband sub-20-fs ultrafast spectroscopy we study the conical intersection dynamics in the visual pigment analog 9-cis Isorhodopsin. We find a longer excited state lifetime and oscillations suggestive of pulsed photoproduct formation. © OSA/ CLEO 2011.